2017
DOI: 10.3201/eid2307.162033
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium gordonae in Patient with Facial Ulcers, Nosebleeds, and Positive T-SPOT.TB Test, China

Abstract: Mycobacterium gordonae is often regarded as a weak pathogen that only occasionally causes overt disease. We report a case of M. gordonae infection in the facial skin, nasal mucosa, and paranasal sinus in an immunocompetent patient and review previous cases. The T-SPOT.TB test might be useful in diagnosing such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…Previous reports have suggested that IGRAs show positive results for infection by NTMs such as M. marinum, M. kansasii, and M. gordonae (1)(2)(3)(4). In the present study, we found that cutaneous tuberculosis and RD1posesssing NTM infections also lead to positive T-SPOT.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous reports have suggested that IGRAs show positive results for infection by NTMs such as M. marinum, M. kansasii, and M. gordonae (1)(2)(3)(4). In the present study, we found that cutaneous tuberculosis and RD1posesssing NTM infections also lead to positive T-SPOT.…”
Section: Discussionsupporting
confidence: 77%
“…Detection of pathogens in skin infections caused by mycobacteria is difficult. Interferon-gamma release assay (IGRA), a preferred method for the diagnosis of latent tuberculosis infection (LTBI), has shown the capacity to detect mycobacterial infections (1)(2)(3)(4). IGRAs have higher specificity over the tuberculin skin test, as they are based on Mycobacterium tuberculosis antigens encoded on RD1 (secretory antigen target 6 and culture filtrate protein 10).…”
mentioning
confidence: 99%
“…Our case demonstrates that M. marseillense can cause infections in immunocompetent persons. For facial skin infection with M. marseillense , this and similar ( 7 ) reports indicate the need for vigilance of paranasal sinus infection. Although many potential virulence factors could be detected by genomic analysis, cases of infection and transmission with this bacterium are rarely reported, suggesting the presence of other influencing factors.…”
mentioning
confidence: 56%
“…gordonae is generally considered a minimally pathogenic mycobacteria. Nonetheless, clinical infections have been reported, even in immunocompetent individuals (6,7). We isolated a distinct strain within the M. gordonae group from a skin infection using whole genome-level approaches based on ANI, is-DDH, and core gene phylogeny.…”
Section: Discussionmentioning
confidence: 99%